GGE biplot analysis of sugar beet multi-environment trials - Ćurčić Živko; Danojević Dario; Mitrović Bojan; Ćirić Mihajlo; Taški-Ajduković Ksenija; Nagl Nevena (Ratarstvo i Povrtarstvo, 2017)
Multi-environment trials are performed every year with the aim of evaluating sugar beet varieties in different environmental conditions of Serbia. The objective of this research was to interpret the effects of genotype, environment and genotype x environment interaction on root yield, sugar content and white sugar yield. GGE biplot method was used to estimate stability of seven sugar beet hybrids developed at the Institute of Field and Vegetable Crops, Novi Sad, Serbia. Mixed model of analysis of variance (ANOVA) was used for the analysis of trial results. Factor genotype effect was assumed fixed while effects of year and environment were assumed random. ANOVA showed that the environment had the greatest effect on root and white sugar yield, while year had the strongest effect on sugar content. Variations of all traits were under significant impact of genotype, while the GEI influence was not a significant. Results of GGE biplot analysis suggested that hybrid Sara was the most stable variety for root yield, while Lara had the greatest stability for sugar content and white sugar yield among the tested genotypes. Also, optimal locations were identified for each genotype, which can be useful when recommending sugar beet varieties for certain growing areas of this field crop.